2017
DOI: 10.1126/science.aaq0186
|View full text |Cite
|
Sign up to set email alerts
|

Early spectra of the gravitational wave source GW170817: Evolution of a neutron star merger

Abstract: On 17 August 2017, Swope Supernova Survey 2017a (SSS17a) was discovered as the optical counterpart of the binary neutron star gravitational wave event GW170817. We report time-series spectroscopy of SSS17a from 11.75 hours until 8.5 days after the merger. Over the first hour of observations, the ejecta rapidly expanded and cooled. Applying blackbody fits to the spectra, we measured the photosphere cooling from [Formula: see text] to [Formula: see text] kelvin, and determined a photospheric velocity of roughly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
230
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(249 citation statements)
references
References 55 publications
18
230
0
1
Order By: Relevance
“…As one of the best sGRB events observed ever, GW170817 is rich in new data; E-mail: hamidani.hamid@yukawa.kyoto-u.ac.jp such as, the mass of the BNS (∼ 2.7M ; Abbott et al 2017a), the viewing angle (∼ 20 • − 30 • ; Abbott et al 2017a;Troja et al 2018), and the delay between the GW and the EM signal (∼ 1.7s; Abbott et al 2017a;Abbott et al 2017c), all inferred for the first time. Superluminal motion in late radio afterglow observations (Mooley et al 2018), and macronova/kilonova (hereafter macronova) emission with a strong support for r-process nucleosynthesis (Arcavi et al 2017;Chornock et al 2017;Coulter et al 2017;Díaz et al 2017;Drout et al 2017;Kilpatrick et al 2017;Kasliwal et al 2017;Nicholl et al 2017;Pian et al 2017;Smartt et al 2017;Shappee et al 2017;Soares-Santos et al 2017;Tanaka et al 2017;Utsumi et al 2017;Valenti et al 2017) are also new revelations. This event also had impacts on the equation of state of neutron stars, relativity, cosmology, etc.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…As one of the best sGRB events observed ever, GW170817 is rich in new data; E-mail: hamidani.hamid@yukawa.kyoto-u.ac.jp such as, the mass of the BNS (∼ 2.7M ; Abbott et al 2017a), the viewing angle (∼ 20 • − 30 • ; Abbott et al 2017a;Troja et al 2018), and the delay between the GW and the EM signal (∼ 1.7s; Abbott et al 2017a;Abbott et al 2017c), all inferred for the first time. Superluminal motion in late radio afterglow observations (Mooley et al 2018), and macronova/kilonova (hereafter macronova) emission with a strong support for r-process nucleosynthesis (Arcavi et al 2017;Chornock et al 2017;Coulter et al 2017;Díaz et al 2017;Drout et al 2017;Kilpatrick et al 2017;Kasliwal et al 2017;Nicholl et al 2017;Pian et al 2017;Smartt et al 2017;Shappee et al 2017;Soares-Santos et al 2017;Tanaka et al 2017;Utsumi et al 2017;Valenti et al 2017) are also new revelations. This event also had impacts on the equation of state of neutron stars, relativity, cosmology, etc.…”
Section: Introductionmentioning
confidence: 93%
“…So far, there has been no estimation of this calibration coefficient for the case of an expanding medium. Matsumoto & Kimura (2018); Salafia et al (2019) used the same calibration coefficient for the case of an expanding medium as an assumption, but offered no evidence. Here, after intense comparison with numerical simulations (in § 3), we found that Mizuta & Ioka (2013) and Harrison et al (2018) findings can be generalized for the case of an expanding medium; for the case of non-relativistic jet head propagation in an expanding medium, we show for the first time that this calibration coefficient is i) necessary and that ii) it takes roughly the same range of values as it does in the collapsar case.…”
Section: A Negligible Ambient Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 shows the rate of brightness change at λ rest ∼ 3400Å as a function of the absolute magnitude (based on the brighter of the two observations used for the rate estimate), while Figure 6 shows the absolute magnitude at λ rest ∼ 3400Å as a function of the time scale of the variability. Figure 7 diagram of other SNe and transients is derived from the u-and b-band light curves of nearby SNe obtained by the Swift Ultraviolet/Optical Telescope (UVOT) (Nugent et al 2011;Brown et al 2012;Pritchard et al 2014), the U -and B-band light curves of SN 1993J (Richmond et al 1994(Richmond et al , 1996, the g-and r-band light curves of PTF 09uj after the shock breakout obtained by PTF (Ofek et al 2010), the g-and r-band light curves of PS1-13arp after the shock breakout and rapid transients obtained by Pan-STARRS1 (Gezari et al 2015;Drout et al 2014), the g-and r-band light curves of the rapidly rising transients obtained by HSC (Tanaka et al 2016), uvw1-, u-, and g-band light curves of a fast luminous ultraviolet transient AT2018cow (Prentice et al 2018;Perley et al 2019), and U -, g-, and r-band light curves of a kilonova (AT2017gfo) associated with a gravitational wave source GW170817 (Andreoni et al 2017;Arcavi et al 2017;Coulter et al 2017;Cowperthwaite et al 2017;Díaz et al 2017;Drout et al 2017;Evans et al 2017;Valenti et al 2017;Kasliwal et al 2017;Pian et al 2017;Shappee et al 2017;Smartt et al 2017;Utsumi et al 2017, summarized in Villar et al 2017. We apply K-corrections by interpolating or extrapolating their spectral energy distributions in magnitude.…”
Section: Comparisons With Known Transientsmentioning
confidence: 99%
“…The X-ray upper limits are given by Swift-XRT and NuSTAR (Evans et al 2017), while the two detections of Chandra are indicated by the red datapoints (Troja et al 2017). For the optical band, we choose r-band to fit and the data are collected in the literature (Andreoni et al 2017;Arcavi et al 2017;Coulter et al 2017;Drout et al 2017;Kilpatrick et al 2017;Pian et al 2017;Shappee et al 2017;Smartt et al 2017). The six radio datapoints (ν = 3 GHz) are taken from Hallinan et al (2017) and could give tight constraints on models.…”
Section: Application To Gw170817/grb170817amentioning
confidence: 99%